Disease specific symptoms indices in patients with celiac disease—A hardly recognised entity - Jabeen, Shaista; Khan, Azmat Ullah; Ahmed, Waqas; Ahmad, Mansur-ud-Din; Jafri, Saghir Ahmad; Bacha, Umar; Ali, Amjed; Muzammil, Hafiz Shehzad; Alsagaby, Suliman A.; Al Abdulmonem, Waleed; Abdelgawad, Mohamed A.; Riaz, Mishal; et al. (Frontiers in Nutrition, 2022)
Celiac disease (CD) considered as rare disease before and was perceivably only limited to children but now effecting almost 1-2% of the global population. This abrupt increase in prevalence is due to advancement in diagnostic criteria and medical facilities but still many countries lack the basic data that can assess the severity of this health issue. The present study was conducted with the aim to assess the common but rarely diagnosed condition with the identification of its underlying secondary ailments.Patients visiting public sector hospitals were recruited and tested for clinical symptoms secondary to gluten containing foods (wheat and barley etc.), followed by serological testing for Immunoglobulin A, tissue transglutaminase A and Anti-endomysial antibodies. Only seropositive candidates were included in the endoscopic and biopsy examination for the features of villous atrophy and intestinal cell damage. The secondary ailments including anemia, growth retardation, and gastrointestinal symptoms were also documented for the tested positive patients. Modified ESPGHAN criterion was followed throughout the study. From 647 suspected cases from March 2018 to July 2019, 113 were confirmed with CD while 58% were female children and 42% were males. Majority of them were from lower class (75%) and 26% of them had positive family history for CD. 67% celiac patients were underweight while wasting was observed in 38% and 80% were stunted as well. From the positive tested CD patients 49% had moderate anemia with 15% having severe anemia. Around 33% had hypoalbuminemia as well. Majority of them had mild to severe range of gastrointestinal symptoms including abdominal pain, diarrhea, flatus, eructation, diarrhea and steatorrhea etc. The study findings indicates an increased number of diagnosed patients of CD with excessive sum of secondary ailments including anemia, growth failure, growth retardation, malnutrition and gastrointestinal symptoms etc.